Hong Kong 2024 - Crowcroft, Orlando; Hui, Angela; O'Malley, Thomas (Lonely Planet guidebooks., 2024)
Lonely Planet's Hong Kong is our most comprehensive guide that extensively covers all the city has to offer, with recommendations for both popular and lesser-known experiences. Sample dim sum in the night market and cruise on the legendary Star Ferry; all with your trusted travel companion.